A kinetic model for Xylella fastidiosa adhesion, biofilm formation, and virulence - Osiro, D.; Colnago, L. A.; Otoboni, AMMB; Lemos, EGM; de Souza, A. A.; Della Coletta, H.; Machado, M. A. (Elsevier B.V., 2004)
Xylella fastidiosa is the causal agent of citrus variegated chlorosis and Pierce's disease which are the major threat to the citrus and wine industries. The most accepted hypothesis for Xf diseases affirms that it is a vascular occlusion caused by bacterial biofilm, embedded in an extracellular translucent matrix that was deduced to be the exopolysaccharide fastidian. Fourier transform infrared spectroscopy analysis demonstrated that virulent cells which form biofilm on glass have low fastidian content similar to the weak virulent ones. This indicates that high amounts of fastidian are not necessary for adhesion. In this paper we propose a kinetic model for X fastidiosa adhesion, biofilm formation, and virulence based on electrostatic attraction between bacterial surface proteins and xylem walls. Fastidian is involved in final biofilm formation and cation sequestration in dilute sap. (C) 2004 Federation of European Microbiological Societies. Published by Elsevier B.V. All rights reserved.
Keywords: Xylella fastidiosa; FTIR; biofilm; Adhesion; virulence